Heterohybridomas producing human immunoglobulin light chains using CD138-selected bone marrow cells - P. Zhou; X. Ma; S. Scalia; D. Toskic; X. Wu; T. Fogaren; Nancy Coady Lyons; Luis del Pozo-Yauner; R.L. Comenzo (Biochemistry and Biophysics Reports)
Background: Light chain research is hampered by lack of mammalian cell lines producing human light chains (FLC). Therefore, we used heterohybridoma (HH) technology to produce clones making FLC thereby providing tools to study light chain behavior. Methods: Marrow CD138+ cells from patients with multiple myeloma (MM) and polyclonal gammopathy (PG) were selected, fused with B5-6 T cells and cultured in hypoxanthine-aminopterin-thymidine medium (HAT). HH clones were selected based on ELISA for human immunoglobulins and flow cytometry for intracellular (IC) FLC. We compared marrow cell counts and HH yields by diagnosis, evaluated clones making only FLC by flow and by dimer/monomer (D/M) ratios in vitro and in vivo, and sequenced FLC genes with RT-PCR. Results: Marrows from 13 patients with active disease, 10 MM and 3 PG, were no different in mononuclear or CD138-selected cell counts. HH FLC clones (7 λ, 1 κ) were obtained from 5/10 MM and 2/3 PG; one PG case produced 2 HH FLC clones (one λ and one κ). Of the 10 MM cases, 8 had high risk cytogenetic features and 4 of the 8 produced HH clones while of the 3 PG cases 2 had negative cytogenetics and 1 had loss of IgH identified and produced an HH clone. Mononuclear (MNC) and CD138-selected cell numbers were markedly higher in the samples that enabled productive fusions. Median MFI for the 8 HH clones by IC flow for FLC was 9849 (range, 5344–27451) and median percentage of cells IC positive was 88 % (69–95). Medians of in vitro and in vivo FLC production were 47 μg/mL (9–80) per million cells after 2 days of culture and 66.4 μg/mL (16–1100) in NOD-SCID γ (NSG) mice 14 days after intraperitoneal (IP) implants of 2 × 106 HH cells. Dimer/monomer ratio medians were 0.575 (0.08–0.939) in vitro and 0.91 (0.82–2.7) in vivo, values that were correlated (R2 = 0.565) by two-tailed paired t-test with P < 0.05. Conclusions: B5-6 T HH producing human FLC were obtained from 50 % of MM and PG cases. High numbers of MNC and CD138+ cells enabled productive fusions. The HH clones produced FLC with easily appreciated dimers and monomers in vitro and in vivo. With IP in vivo implants after 2 weeks more dimers were seen than in short term cultures in vitro. These HH clones will be made available for study of FLC metabolism and testing of therapeutics designed to abrogate FLC production or enable FLC clearance in vivo.